Lugares y políticas de la memoria: notas teórico-metodológicas a partir de la experiencia Argentina - Messina, Luciana Silvia (2019)
The aim of this paper is to study some substantive aspects into the relationship between memories, politics and places in the field of memory studies. The proposal that guides it is to advance in the construction of a theoretical and conceptual framework for the analysis of different strategies of spacialization of social memory related to actors and events of pasts of state violence and political repression, with focus on the argentine case. To this end, a bibliography of a different nature that has worked on the subject has been critically reviewed in order to distinguish the concepts and analytical dimensions that are relevant in the construction of research objects (material, symbolic, pedagogical, political, and public). Likewise, the article recovers and analyzes the tensions, debates and controversies that emerge in the making of memory spaces and proposes ways of entry for its analysis.